2015
DOI: 10.1017/s0007114515000884
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxytyrosol improves mitochondrial function and reduces oxidative stress in the brain ofdb/dbmice: role of AMP-activated protein kinase activation

Abstract: Hydroxytyrosol (HT) is a major polyphenolic compound found in olive oil with reported anti-cancer and anti-inflammatory activities. However, the neuroprotective effect of HT on type 2 diabetes remains unknown. In the present study, db/db mice and SH-SY-5Y neuroblastoma cells were used to evaluate the neuroprotective effects of HT. After 8 weeks of HT administration at doses of 10 and 50 mg/kg, expression levels of the mitochondrial respiratory chain complexes I/II/IV and the activity of complex I were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 54 publications
4
56
0
1
Order By: Relevance
“…Our transcriptomic analysis confirms previous results from our group [13] and those of other groups [23][24][25] pointing towards physiological effects of HT on oxidation-reduction processes. We now provide evidence that, in the small intestine, long-term HT supplementation also influences these pathways.…”
Section: Discussionsupporting
confidence: 91%
“…Our transcriptomic analysis confirms previous results from our group [13] and those of other groups [23][24][25] pointing towards physiological effects of HT on oxidation-reduction processes. We now provide evidence that, in the small intestine, long-term HT supplementation also influences these pathways.…”
Section: Discussionsupporting
confidence: 91%
“…To counteract such effect and enhance oxidative metabolism, HT was supposed to be a good candidate. Although no clinical trial investigated the effect of HT supplementation, studies in obese- and diabetic-rendered rats and in doxorubicin-induced cardiotoxicity rats revealed that HT (0.5, 10 and 50 mg/kg/day) is able to increase mitochondrial function through an enhancement of mitochondrial complex subunit expression [65,105] and activity [105,106]. Enhanced mitochondrial activity was associated with an increase of uncoupling protein-2 protein expression (100 µM) [107].…”
Section: Associated Complications: Oxidative Stress Inflammationmentioning
confidence: 99%
“…Accordingly, HT was shown to improve the mitochondrial electron transport chain in rats with cardiotoxicity induced by doxorubicin by increasing the levels of complex-II and complex-III that partially restore the respiratory chain activity [38]. This effect was also observed in diabetic mice after a 2-month treatment with HT at doses of 10 and 50 mg/kg, where the expression levels of complexes I, II, and IV and the activity of complex I were increased in the brain, improving mitochondrial function [15]. In agreement with these views, HT also stimulates mitochondrial biogenesis in ARPE-19 human retinal pigment epithelial cells subjected to OS, through enhancement in the expression of PGC1α that leads to an increased protein expression of mitochondrial transcription factor A, uncoupling protein 2 (UCP2) and mitochondrial complexes [40] (Table 1).…”
Section: Protective Properties Of Hydroxytyrosolmentioning
confidence: 97%
“…HT is known to improve mitochondrial function either by increasing the activity and/or expression of mitochondrial complexes I, II, III, IV, and V [15,38,59,60]. The 3T3-L1 adipocytes subjected to HT in the concentration range of 0.1–10 μM stimulated the expression and activity of peroxisome-proliferator activator receptor γ co-activator 1α (PGC1α), which promotes mitochondrial function by increasing the expression and activity of all complexes involved in the respiratory chain and oxidative phosphorylation [60].…”
Section: Protective Properties Of Hydroxytyrosolmentioning
confidence: 99%
See 1 more Smart Citation